Premature Atherosclerotic Cardiovascular Disease: Trends in Incidence, Risk Factors, and Sex‐Related Differences, 2000 to 2016. Issue 14 (16th July 2019) - Vikulova, Diana N.; Grubisic, Maja; Zhao, Yinshan; Lynch, Kelsey; Humphries, Karin H.; Pimstone, Simon N.; Brunham, Liam R.
Abstract : Background: The incidence of atherosclerotic cardiovascular disease has declined in the past 2 decades. However, these benefits may not extend to young patients. The objective of this work was to assess temporal trends in the incidence, risk profiles, sex‐related differences, and outcomes in a contemporary population of young patients presenting with coronary artery disease (CAD) in British Columbia, Canada. Methods and Results: We used a provincial cardiac registry to identify young patients (men aged <50 years, women aged <55 years), with a first presentation of CAD between 2000 and 2016, who had either ≥50% stenosis of ≥1 coronary arteries on angiography or underwent coronary revascularization. A total of 12 519 patients (30% women) met our inclusion criteria. The incidence of CAD remained stable and was higher for men than women (46–53 versus 18–23 per 100 000). Of patients, 92% had at least one traditional cardiovascular risk factor and 67% had multiple risk factors. The prevalence of diabetes mellitus, obesity, and hypertension increased during the study period and was higher for women. Women had fewer emergent procedures and revascularizations. Mortality rates decreased by 31% between 2000 and 2007, then were stable for the remaining 9 years. Mortality was significantly higher for women aged <45 years compared with men. Conclusions: The incidence of premature CAD has not declined, and the prevalence of 3 major cardiovascular risk factors increased between 2000 and 2016. The risk burden and mortality rates were worse for women. These data have important implications for the design of strategies to prevent CAD in young adults.